Use of a Tablet Attachment in Teleophthalmology for Real-Time Video Transmission from Rural Vision Centers in a Three-Tier Eye Care Network in India: eyeSmart Cyclops. (1st April 2019) - Loomba, Abhinav; Vempati, Sandeep; Davara, NavyaDeepthi; Shravani, M.; Kammari, Priyanka; Taneja, Mukesh; Das, Anthony Vipin
Abstract : Purpose. This study describes the development of an attachment for a smart tablet to stream live video information of an eye examination through the slit lamp. Methods. A tablet attachment was developed that enables the live streaming of video from the slit lamp from the rural vision centers of the LVPEI network. A video streaming solution like Skype Lite was used to transmit the same. The eyeSmart app was utilized for the documentation of the clinical information of the patients. Results. A tablet attachment of eyeSmart Cyclops was developed and piloted in 3 vision centers of the LVPEI network. Conclusion. The use of real-time video transmission illustrates a novel teleophthalmology solution in low resource settings to screen rural populations. The ability to transmit live video enables gathering more information than static images.